2014
DOI: 10.1007/s12033-014-9774-9
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Retention of Thermostability and Specific Activity in Chimeric Human Alkaline Phosphatases

Abstract: Alkaline phosphatases (APs) are a family of dimeric metalloenzymes that has been utilized in many areas due to its ability to hydrolyze a variety of phosphomonoesters. While mammalian APs have higher specific activity than prokaryotic APs, they are generally less thermostable. To cultivate the possibility to confer mammalian APs with higher thermostability as well as high activity, we focused on human AP isozymes. Among the four isozymes of human APs, placental AP (PLAP) retains the highest thermostability, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…It has been reported that the successive domains of protein G can increase the affinity to antibodies, and the addition of protein A in between protein G and the enzymatic domain can preserve the activities of each protein . As an alkaline phosphatase (AP) part, chimera alkaline phosphatase (IPP) composed of intestinal AP and placental AP was employed . The MTG-recognizable K-tag (MRH K GS) was introduced to the C-terminus of IPP-PG (Ktag-IPP-PG).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the successive domains of protein G can increase the affinity to antibodies, and the addition of protein A in between protein G and the enzymatic domain can preserve the activities of each protein . As an alkaline phosphatase (AP) part, chimera alkaline phosphatase (IPP) composed of intestinal AP and placental AP was employed . The MTG-recognizable K-tag (MRH K GS) was introduced to the C-terminus of IPP-PG (Ktag-IPP-PG).…”
Section: Resultsmentioning
confidence: 99%
“…50 As an alkaline phosphatase (AP) part, chimera alkaline phosphatase (IPP) composed of intestinal AP and placental AP was employed. 51 The MTG-recognizable K-tag (MRHKGS) was introduced to the C-terminus of IPP-PG (Ktag-IPP-PG). After the confirmation of the produced protein showing the specific detection of biomolecules, the conjugation with the Z-QG polymer was examined.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Synthetic polymers containing the N-benzyloxycarbonyl-L-glutaminylglycine (Z-QG) motif have been used as scaffolds to conjugate numerous enzyme units via MTG-catalyzed conjugation reactions. A chimeric molecule comprising alkaline phosphatase (IPP), 47 pG (IPP-PG), and a K-tag (MRHKGS) was grafted onto the Z-QG polymer using MTG (Fig. 3A).…”
Section: •1 Transglutaminase-catalyzed Formation Of Polymericmentioning
confidence: 99%
“… 87 , 88 Currently, the combination treatment is being attempted. In addition, a recent successful attempt of ERT in Akp2 −/− mice using a soluble chimeric alkaline phosphatase, which is a chimeric molecule of human intestinal alkaline phosphatase with the crown domain of human PLAP, 89 showed therapeutic benefit of the nonmineral-targeting recombinant enzyme. 90 Another method to reduce the injection burden is gene therapy, especially ex vivo gene therapy into bone marrow stem cells.…”
Section: A Possible Role Of Asfotase Alfamentioning
confidence: 99%